THE ROLE OF JOB ANALYSIS ON ORGANIZATIONAL CULTURE IN THE PERSPECTIVE OF HUMAN RESOURCE MANAGEMENT AT ARTEE LAW OFFICE: PERAN JOB ANALYSIS TERHADAP BUDAYA ORGANISASI DALAM PERSPEKTIF MANAJEMEN SUMBER DAYA INSANI DI ARTEE LAW OFFICE - Uyun, Siti Eniyatul; Najib, Try Ma’rifan; Thayib, Thayib (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2023)
Job analysis is an important part of human resource management activities. Because one of the things that delivers organizational success is the existence of accurate data about the profile of each position, the type of skills and abilities needed as well as the experience and education required to occupy a position and can create a positive organizational culture. Organizational culture can be defined as a set of systems, values, beliefs, assumptions or norms that have been relatively long in force, agreed upon and followed by all members of the organization As behavioral norms in solving organizational problems. This study aims to determine the role of job analysis on organizational culture in the perspective of human resources at Artee Law Offiice. This research method uses qualitative research methods and the data sources used in this study use primary data sources and secondary data. So that the data collected apart from books, journals, websites are also sourced from the results of interviews conducted by researchers. The results of this study can be concluded by the existence of job analysis which consists of two main parts, namely job description and job specification able to maximize the potential of human resources owned. So that the job analysis is also able to create a positive organizational culture because all parties involved such as lawyers, paralegals and management have their own job descriptions and job specifications.